ANALISIS MINAT BELAJAR MATEMATIKA SISWA PADA PEMBELAJARAN TATAP MUKA DI MASA PANDEMI COVID-19 - Mahmudah Titi Muanifah; Trisniawati Trisniawati; Nelly Rhosyida; Retno Anggraheni (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
Abstract This study aims to determine students interest in learing mathematics in face-to-face learning during the covid-19 pandemic. The research method used is a qualitative descriptive method of phenomenology with the research subject of 11 student in grade 5 SD Negeri Sumberharjo, Pacitan. The data collection technique used a closed questionnaire and was given using a google form. The data analysis technique was carried out using a Likert scale and then the obtained questionnaire scores were analyzed. The result showed that the interest in learning mathematics in grade 5 SD Negeri Sumberharjo in face-to-face learning during the covid-19 pandemic was in the high category of 90%, while the rest were in the medium category.